Machiavelli on arte dello stato - Prašević, Nedžib M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
In his extraordinary studies From Politics to Reason of State, Professor Maurizio Viroli (1992) pointed out the moment when the ancient notion of politics was replaced with the Renaissance and new century understanding of reason of state. What was left out of the research was the fact that the political theory register introduced a new term which explains this transition and derogation from the classical notion of politics. The Machiavellian term arte dello stato describing actions of agents of politics, represents a revolutionary innovation, and this is the process whose development I wish to address in this paper, as well as explain what it means. Finally, with regard to the historical context I aim to show that it is precisely the practice of the political agents of the time that Machiavelli used to frame the new idea.
Keywords: arte dello stato; arte; stato; politics; Cosimo Medici; Savonarola